Ginsenoside Rb1 exerts antidepressant-like effects via suppression inflammation and activation of AKT pathway. (23rd January 2021) - Guo, Ying; Xie, Jianping; Zhang, Lanchun; Yang, Lingli; Ma, Jiaqing; Bai, Yufan; Ma, Wenjie; Wang, Ling; Yu, Haofei; Zeng, Yueqin; Luo, Haiyun; Zhang, Rongping
Highlights: GRb1 had an antidepressant effects via relieving the depression-like behaviors in CRS model. GRb1 plays a crucial role in the anti-inflammatory and protection of microglia. GRb1 has potential to treat wider range of patients with depression. Abstract: Depression-like behaviors caused by chronic stress are related to inflammation and microglia activation. Antidepressant therapy may contribute to inhibiting inflammation responses and microglia activation. Ginsenoside Rb1 (GRb1) is known to display antidepressant-like effect on chronic unpredictable mild stress-induced depressive rats. However, the antidepressant-like effects of GRb1 on chronic restraint stress (CRS) mice and the potential anti-inflammatory mechanisms are unclear. Here, we focused on the molecular mechanisms related to inhibition of inflammation response and the protection on microglia. Our results showed that GRb1 had an antidepressant effects via relieving the depression-like behaviors in CRS model. Furthermore, GRb1 increased the protein expressions of brain-derived neurotrophic factor and phospho- protein kinase B/ protein kinase B (p-AKT/AKT), and decreased the protein expressions of interleukin-1β (IL-1β), tumor necrosis factor α (TNF-α) and ionized calcium binding adapter molecule 1 in hippocampus, reduced the levels IL-1β and TNF-α in serum. Finally, GRb1 lowered the protein expressions of IL-1β and TNF-α in BV-2 microglia induced by lipopolysaccharides. Taken together, the results indicate that GRb1 prevents CRS-induced depression-like behaviors in mice, which may be related to anti-inflammatory effects in hippocampus, serum and microglia and activation of AKT pathway.